Influence Behavior Toward Consumer Buying Decisions In House Type 36. Lagan Pangka Pekanbaru - Azhari Azhari (Universitas Pendidikan Ganesha, 2017)
The purpose of this study was to determine whether the factor of cultural, social, personal and psychological Influential Home Buying Decision Against Type 36 PT. Lagan PangkaPekanbaru. Data analysis technique using multiple linear regression analysis. The samples used were 58 respondents with accidental sampling technique. Data collection techniques by questionnaire. Based on the results of this study concluded that the factor of cultural, social, personal and psychological significantly influence the purchase decision Houses Type 36 PT. Lagan PangkaPekanbaru. Test the correlation coefficient (R) independent variable on the dependent variable are very strong closeness of 0.951 and a contribution of independent variables on the dependent variable (R2) was 89,70%Keywords : Factor Culture, Social, Personal, Psychological and Purchase Decision